Treatment of oil-in-water emulsion using tubular ceramic membrane acquired from locally available low-cost inorganic precursors. Issue 58 (13th December 2016) - Vinoth Kumar, R.; Monash, P.; Pugazhenthi, G.
Abstract: This article highlights the fabrication of ceramic membrane with tubular configuration using locally available inexpensive clays and its application in oil-in-water emulsion treatment. Extrusion technique was employed to manufacture the tubular-shaped ceramic membrane having length, outer, and inner diameters of 100, 12, and 6.5 mm, respectively. Clay powders and the fabricated membrane were characterized using standard techniques such as particle size distribution, scanning electron microscopy, energy dispersive X-ray spectroscopy, X-ray diffraction, thermogravimetric (TG), and field emission scanning electron microscopy analysis. The fabricated membrane possessed porosity of 50%, average pore diameter of 0.339 μm, and mechanical strength of 12 MPa with relatively good corrosion resistance in acidic and basic conditions. The effect of various operating conditions such as pressure (69–345 kPa) and cross-flow velocity (0.044–0.132 m/s) on the microfiltration process of oil-in-water emulsion was studied using this membrane with a fixed feed oil concentration of 100 mg/L in a cross flow manner. The research findings indicated that the rejection of oil slightly decreased with the rise in pressure. The best rejection of 99.88% was obtained with permeate flux of 3.40 × 10 −5 m 3 /m 2 s at an applied pressure of 68 kPa after 1 h of experimental run. These results demonstrated the application of the fabricated membrane in oil-in-water emulsion treatment and the treated water can be directly discharged into water bodies. Finally, the estimation of the manufacturing cost of the acquired membrane was presented in detail.